Aspek afektif: Aspek afektif - Maryam Paso; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
The development of computer technology and human-computer interaction in the 21st century has led to increased attention to affective aspects. The affective aspect involves understanding and recognizing human emotions and the use of emotional information in human and computer interactions. Recent studies show that affective aspects play an important role in enhancing user experience and user satisfaction. Facial recognition, voice analysis and motion detection are used to identify and monitor the user's emotions. However, there are challenges that need to be overcome, such as developing algorithms and computational models that are accurate in recognizing and responding to human emotions, as well as ethical considerations in the use of emotional data. Affective aspects also have an important impact on education, with attitude assessment covering aspects of receiving, responding, assessing, managing, and living. Attitudes are learning outcomes that can be influenced, directed, and shaped in education. Through the development of affective aspects, it is expected to create a computer interface that is more humane, responsive, and meets the emotional needs of users. Further research and development in this field is expected to have a positive impact on future computer users, create a more empathetic and emotionally connected computing experience, and improve the quality of human life in this digital era.